Searching for the Natural Rate of Interest: a Euro-Area Perspective - Jesus Crespo Cuaresma; Ernest Gnan; Doris Ritzberger-Grünwald (Oesterreichische Nationalbank (OeNB), 2003)
A time-varying natural rate of interest is estimated for the euro area using a multivariate unobserved components model. The problem of aggregating interest rate data for the pre-EMU period is directly addressed, and a simple method in order to adjust the risk premia in the interest rate data prior to 1999 is proposed. We show that, for the pre-EMU period, using risk-unadjusted policy rates leads to periods of high risk premia being erroneously taken as monetary policy replies to the output gap; by contrast, using risk-adjusted policy rates yields an estimate of the reaction of monetary policy to the output gap corresponding approximately to an increase of 40 basis points for a 1% positive deviation of output from potential output. A positive deviation of inflation from its trend of 1% is estimated to have triggered approximately a 1.2% increase in short-term interest rates.
Keywords: E43; E52; C32; 330; Natural rate of interest; unobserved components models; monetary policy; Taylor rule